(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the impact of the solar radiation flux returned from the Earth’s surface on the radiation field in the atmosphere was studied using theoretical calculations. It is considered that the intensity of the luminous flux returned from the earth’s surface is distributed according to Lambert’s law, and the method of calculating the amount of this flux was developed based on the theory of S-matrices. The influence of the Earth’s surface return coefficient on diffuse and unscattered fluxes from the atmosphere to space and the Earth’s surface was calculated. Calculations were carried out taking into account the full spectrum of the solar radiation flux.